Respuesta :
Answer:
-7
Step-by-step explanation:
The equation is in the form
ax^2 +bx +c =0
x^2 -x+2=0
a=1 b=-1 c =2
The discriminant is
b^2-4ac
(-1)^2-4(1)(2)
1-8
-7
For this case we must find the discriminant of the following quadratic equation:
[tex]x ^ 2-x + 2 = 0[/tex]
Its roots will be given by:
[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}[/tex]
Where:
[tex]a = 1\\b = -1\\c = 2[/tex]
By definition, the discriminant is given by:
[tex]b ^ 2-4 (a) (c) = (- 1) ^ 2-4 (1) (2) = 1-8 = -7[/tex]
Answer:
The discriminant is -7